Rhyme and Reason: Exploring Textual Lens in Nursery Rhyme Songs - Menes, Aj; Dimaculangan, Dustin Macky; Tenedero, Cynic; Lagria, Cyrus Lian; Ogong, Nino Kashmer; Pelimer, Adrian; Espinosa, Jie Anne (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2025)
This study examined the linguistic and metadiscourse features in children's English nursery rhymes using Text Inspector. The researchers conducted an analysis of eight (8) nursery rhymes which meet some basic criteria for rhyme and rhythm, and playing a considerable part in developing early language and literacy skills. The study highlights the use of repetition as a mnemonic and engagement tool, which helps cement the material in the memory while maintaining the interest of young children. The songs were provided for metadiscourse analysis to illustrate how markers, which signify linguistic features, such as logical connectives, sequential words, relational markers, and personal pronouns, support increased phonological awareness, language enrichment, and cognitive development. Findings showed that nursery rhymes naturally contain interactive metadiscourse features such as repetition, sequence, and structure, which facilitate comprehension and promote active participation among young learners. The nursery rhymes that develop many skills besides logical connectedness are "Baa, Baa, Black Sheep", "Wheels on the Bus", "If You're Happy and You Know It", “Jack and Jill”, 'Twinkle, Twinkle Little Star”, and “Five Little Monkeys”. While songs such as “Apple and Bananas” and “London Bridge” were particularly rich in logical connectives, which lend predictability to the rhythm of the rhymes while also supporting memory retention. However, the limited use of personal markers stressed that the rhymes are more structural than referential. Ultimately, nursery rhymes are not only rich in culture but also pedagogically relevant to support language and literacy development, especially through storytelling, rhythm, and play. The researchers recommend to further examine nursery rhymes in other languages to study metadiscourse from a broader cultural perspective.